Wind farm and environmental aerodynamics assessment using computational engineering - Zoumprouli, Argyro (Cranfield University, 2011)
The aim of this thesis is the application of computational engineering software for the study of wind resource assessment of a wind farm as well as for establishing the range of influence of different numerical and physical parameters, including turbulence modeling , surface roughness and wakes. Simulations were performed for a wind farm which is in operation since 2006, called Panachaiko, located at the west part of Greece and encompassing an energy capacity of 34.85 MW. Simulations were performed using three variants of the k-ε model. Moreover, the effects of surface roughness and wake on the efficiency of wind farm operation were investigated. Comparisons were performed between linear and non-linear computational fluid dynamics (CFD) modeling, in the framework of the available engineering (commercial) software. Both qualitative and quantitative assessment of the results is presented. The study revealed the dependence of the results on the CFD (linear vs non-linear) model employed. The results of the present study provide useful guidance regarding the applicability of CFD models for wing resource assessment.